UPACARA PANGANTEN DAYAK KANAYATN KABUPATEN LANDAK KECAMATAN MEMPAWAH HULU DALAM PERSPEKTIF AL-‘URF - Pratama, Rizky; Marluwi, Marluwi; Wibowo, Arif (Al-Usroh, 2025)
This study aims to examine: (1) Which marriage customs are still practiced by the Dayak Kanayatn tribe today, and (2) The Islamic legal perspective on the implementation of the Dayak Kanayatn wedding ceremony based on the concept of al-‘urf for Muslim adherents. This research employed a qualitative field research method, utilizing direct observation and in-depth interviews as primary data collection techniques. The primary data were obtained through documented interviews with key informants, including two traditional leaders and one religious figure, while secondary data were gathered from relevant books, articles, and scholarly sources. Data collection was conducted through interviews and documentation, and data validity was ensured through triangulation. The findings indicate that (1) The marriage customs currently practiced by the Dayak Kanayatn tribe are Picaraatn, Ngomok, and the Wedding Feast, each involving a picara (spokesperson) and a paraga tool used as a medium for prayer to Jubata (God); and (2) From the perspective of al-‘urf in Islamic jurisprudence, the practice of this wedding ceremony is considered contrary to Islamic teachings when performed by Muslims and is classified as ‘urf fasid (corrupt custom) due to elements of shirk (polytheism), the permissibility of prohibited acts (such as the slaughter of pork), and the risk of leading to fornication if conducted prior to a valid Islamic marriage contract. Consequently, the practice is deemed haram (forbidden) under Islamic law, as it contradicts core principles of tawhid and Sharia, despite certain elements like Picaraatn being individually permissible, since the entire ceremony is inseparable and embedded within practices that violate Islamic doctrine.